Possibilities of using management variable and wage productivity for bankruptcy prediction of Polish enterprises - Jędrzejczyk, Marcin; Klimek, Aleksander (Możliwości wykorzystania zmiennej zarządzania i produktywności pracy do predykcji bankructwa polskich przedsiębiorstw, 2019)
The risk of bankruptcy of an enterprise is inevitably inscribed in running a business. This risk should be managed effectively in order to avoid negative consequences associated with the bankruptcy of an entity. This article will present the economic and legal causes of bankruptcy, followed by its negative and positive effects. In connection with this topic, the authors will discuss the concept of the microeconomic wage productivity and the management variable in the context of their importance in an enterprise. As an extension of previous studies by one of the authors, an attempt will be made to determine the possibility of applying the microeconomic wage productivity and the management variable as a supplement of the bankruptcy risk analysis of enterprises that are suppliers to the automotive industry in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 4, s. 81-94
Keywords: causes of bankruptcy; consequences of bankruptcy; wage productivity; management Variable; przyczyny bankructwa; skutki upadłości; produktywność pracy; zmienna zarządzania; bankructwo; upadłość